Towards a comprehensive transient model of a large five-legged transformer under no-load conditions - Zirka, Serhii; Albert, Dennis (Challenges and Issues of Modern Science, 2024)
Large power transformers are related to the most responsible and expensive elements of electrical networks. Long-term operation of transformers without shutdowns requires taking into account energy losses in these devices and places high demands for the reliability of their modeling. The aim of this paper is to improve the dynamic model of a five-legged three-phase transformer used to reduce the overall height of the apparatus. The model under consideration develops the models and methods described earlier. The proposed improvements consist in a more detailed reproduction of the transformer operation under the no-load conditions at rated and increased supply voltage. The accuracy of the model is achieved by taking into account the hysteresis properties of the core, equivalent phase capacitances, and nonmagnetic gaps between the legs and yokes. The model's capabilities are illustrated by simulating a large five-legged transformer.The object of study of this paper is the modeling of a 786 MVA step-up generator transformer and winding connection Yd11. The inner low voltage (LV) winding is connected in delta (d) with the liner voltage of 28 kV, whereas the liner voltage of the wye-connected (HV) outer winding (Y) is 525 kV. The rest of the transformer parameters are given in the literature.The intermediate objective of the study is to model the transformer no-load losses in a wide range of LV. The second and main stage of the work is to reproduce the current waveforms in the three-phase line feeding the LV winding (the model has to cover LV voltages that reach 110% of the nominal value). It should be noted that the problem of calculating the current waveform was posed earlier, but no typical current curves were found in that work, and its authors limited themselves to modeling the transformer at rated voltage.